2022
DOI: 10.3389/fimmu.2022.874978
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Molecular Correlations Between DHRS4 and Progressive Neurodegeneration in Amyotrophic Lateral Sclerosis By Gene Co-Expression Network Analysis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease, and its candidate biomarkers have not yet been fully elucidated in previous studies. Therefore, with the present study, we aim to define and verify effective biomarkers of ALS by bioinformatics. Here, we employed differentially expressed gene (DEG) analysis, weighted gene co-expression network analysis (WGCNA), enrichment analysis, immune infiltration analysis, and protein–protein interaction (PPI) to identify biomarkers of ALS. To valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Cd74 deficiency could decrease peripheral lymphocyte activation and neurodegeneration following TBI, suggesting that targeting the switch between innate and adaptive immunity might be a potential therapeutic strategy [45]. C1qa, C1qb, and C1qc are three distinct subunits of complement component C1q, which is a crucial protein in the complement cascade within the innate immune system [71,72]. One recent clinical study showed that elevated serum C1q levels were significantly correlated with traumatic severity and could serve as an independent prognostic factor for long-term outcomes after TBI [73].…”
Section: Discussionmentioning
confidence: 99%
“…Cd74 deficiency could decrease peripheral lymphocyte activation and neurodegeneration following TBI, suggesting that targeting the switch between innate and adaptive immunity might be a potential therapeutic strategy [45]. C1qa, C1qb, and C1qc are three distinct subunits of complement component C1q, which is a crucial protein in the complement cascade within the innate immune system [71,72]. One recent clinical study showed that elevated serum C1q levels were significantly correlated with traumatic severity and could serve as an independent prognostic factor for long-term outcomes after TBI [73].…”
Section: Discussionmentioning
confidence: 99%
“…The fast development of bioinformatics provides a broad prospect for the research of disease diagnosis and therapeutic targets [26]. For example, Lee et al found that DLK2 acts as a potential prognostic biomarker for RCC based on bioinformatics analysis [27].…”
Section: Introductionmentioning
confidence: 99%